Artificial intelligence as a learning assistant: A student-centered learning study - Lee, Bih Ni (Jurnal Cakrawala Pendidikan, 2026)
This study examines the role of Artificial Intelligence (AI) as a learning assistant in promoting student-centered learning within educational settings. Using a mixed-method approach, the research investigates how AI-based tools support personalized learning, enhance student engagement, and foster autonomy in the learning process. Quantitative data were collected through structured surveys and learning performance measures to evaluate students’ perceptions, usage patterns, and learning outcomes, whereas qualitative data derived from interviews and open-ended responses provided deeper insights into students’ experiences and challenges when interacting with AI learning assistants. The findings indicate that AI learning assistants positively contribute to individualized learning support, timely feedback, and active learner participation, although issues related to overreliance, ethical concerns, and digital readiness remain. The study highlights the potential of AI as an effective facilitator of student-centered learning when thoughtfully integrated into instructional design and pedagogical practices.